Subtypes of Australia antigen (HBsAg) in leprosy - Ottati, Sandra (1979)
One hundred and thirty five sera from patients with leprosy were tested for the ad and ay subtypes of HBsAg. Only three (2,2%) had HBsAg and all were ad positive.